Забезпечення продуктивності діяльності Call Center - Сабурова, С. О.; Радченко, Р. В.; Кадацька, О. І. (ХНУРЕ, 2022)
The subject of research is automation of business processes of the information system CALL CENTER CTI CRM. The aim is reengineering of business processes of the CALL CENTER information system CTI CRM, methods of structural and object - oriented analysis and design. The purpose of the work is to develop an information system and methods for testing the quality parameters of the CALL CENTER CTI CRM. Research and modeling methods, were used to solve specific practical problems, namely to solve problems of efficiency of CALL CENTRE CTI CRM of the PSTN in terms of interaction with the Internet, cloud computing and some methods of monitoring the efficiency of access resources on the example of the proposed software interfaces.
Keywords: Call Center; KPI